Reverse Engineering Static Content and Dynamic Behaviour of E-Commerce Websites for Fun and Profit - João Pedro Matos Teixeira Dias (2016)
Nowadays electronic commerce websites are one of the main transaction tools between on-line merchants and consumers or businesses. These e-commerce websites rely heavily on summarizing and analyzing the behavior of customers, making an effort to influence user actions towards the optimization of success metrics such as CTR (Click through Rate), CPC (Cost per Conversion), Basket and Lifetime Value and User Engagement. Knowledge extraction from the existing e- commerce websites datasets, using data mining and machine learning techniques, has been greatly influencing the Internet marketing activities.When faced with a new e-commerce website, the machine learning practitioner starts a web mining process by collecting historical and real-time data of the website and analyzing/transforming this data in order to be capable of extracting information about the website structure and content and its users' behavior. Only after this process the data scientists are able to build relevant models and algorithms to enhance marketing activities.This is an expensive process in resources and time since it will always depend on the condition in which the data is presented to the data scientist, since data with more quality (i.e. no incomplete data) will make the data scientist work easier and faster. On the other hand, in most of the cases, data scientists would usually resort to tracking domain-specific events throughout a user's visit to the website in order to fulfill the objective of discovering the users' behavior and, for this, it is necessary to perform code modifications to the pages themselves, that will result in a larger risk of not capturing all the relevant information by not enabling tracking mechanisms in certain pages. For example, we may not know a priori that a visit to a Delivery Conditions page is relevant to the prediction of a user's willingness to buy and therefore would not enable tracking on those pages.Within this problem context, the proposed solution consists in a methodology capable of extracting and combining information about a e-commerce website through a process of web mining, comprehending the structure as well as the content of the website pages, relying mostly on identifying dynamic content and semantic information in predefined locations, complemented with the capability of, using the user's access logs, extracting more accurate models to predict the users future behavior. This allows for the creation of a data model representing an e-commerce website and its archetypical users that can be useful, for example, in simulation systems.